Interactions Between Ultraviolet B Radiation, Warming, and Changing Nitrogen Source May Reduce the Accumulation of Toxic Pseudo-nitzschia multiseries Biomass in Future Coastal Oceans - Kelly, Kyla J.; Fu, Fei-Xue; Jiang, Xiaowen; Li, He; Xu, Dong; Yang, Nina; DeMers, Michelle A.; Kling, Joshua D.; Gao, Kunshan; Ye, Naihao; Hutchins, David A. (Frontiers in Marine Science, 2021)
Understanding the environmental conditions that trigger Pseudo-nitzschia bloom formation and domoic acid (DA) production is critical as the frequency and severity of these toxic blooms increases in the face of anthropogenic change. However, predicting the formation of these harmful blooms in a future ocean remains a challenge. Previous studies have examined the effects of single environmental drivers on Pseudo-nitzschia spp. growth and toxin production, but few have considered the interactions between them. In this multiple driver study with Pseudo-nitzschia multiseries, we used a full factorial matrix experimental design to examine the simultaneous effects of temperature (20 and 25°C), nitrogen source (nitrate and urea), and irradiance (photosynthetically active radiation with and without ultraviolet B radiation; UVB). This strain of P. multiseries was unable to withstand prolonged exposures (>0.5 h) to 0.06 mw⋅cm–2 UVB light, with implications for near-surface bloom formation if future shallower mixed layers increase UVB exposure. Growth rates were inhibited by UVB, but photosynthesis and carbon fixation continued at a reduced capacity. Additionally, DA synthesis continued despite UVB-induced growth inhibition. Warming by 5°C enhanced cellular DA quotas three-fold. Within these warmer treatments, urea-grown cultures exposed to UVB had the highest amount of DA per cell, suggesting that interactive effects between UVB exposure, warming, and urea can synergistically enhance toxin production. However, overall production of toxic biomass was low, as growth-integrated DA production rates were near zero. This indicates that although Pseudo-nitzschia multiseries cell-specific toxicity could worsen in an anthropogenically-altered future ocean, bloom formation may be inhibited by increased exposure to UVB. This multi-variable experimental approach revealed previously unknown interactions that could not have been predicted based on combined effects of single-variable experiments. Although P. multiseries DA production may be enhanced in a future ocean, inherent sensitivity to prolonged UVB exposure may moderate trophic transfer of toxin to coastal food webs.